2002
DOI: 10.1073/pnas.182552499
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus EBNA2 blocks Nur77- mediated apoptosis

Abstract: Epstein-Barr virus infection in vitro immortalizes primary B cells.EBNA2 is an Epstein-Barr virus-encoded transcriptional transactivator that mimics the effects of activated Notch signaling and is essential for this proliferative response. An assay using Sindbis virus (SV) as a cell death inducer revealed that, like Notch, EBNA2 also has antiapoptotic activity. We show that Nur77 is a mediator of SV-induced cell death and that EBNA2 antiapoptotic activity results from interaction with Nur77. EBNA2 colocalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 72 publications
1
63
0
Order By: Relevance
“…After ligand binding, the intracellular domain of NOTCH (N IC ) is released by a series of proteolytic events involving c-secretase followed by translocation to the nucleus where it forms a ternary transcription factor complex on CSL (for CBF1, Suppressor of Hairless and LAG-1) responsive genes (Kovall, 2008). Besides its role as a transcription factor, NOTCH modulates various cancer relevant signal transduction pathways including nuclear factor (NF)jB (Osipo et al, 2008) and NR4A1 (Lee et al, 2002). NOTCH gain of function mutations are tumourigenic by rendering transformed cells into a less-differentiated immortalized state (Leong & Karsan, 2006;Miele, 2006;Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After ligand binding, the intracellular domain of NOTCH (N IC ) is released by a series of proteolytic events involving c-secretase followed by translocation to the nucleus where it forms a ternary transcription factor complex on CSL (for CBF1, Suppressor of Hairless and LAG-1) responsive genes (Kovall, 2008). Besides its role as a transcription factor, NOTCH modulates various cancer relevant signal transduction pathways including nuclear factor (NF)jB (Osipo et al, 2008) and NR4A1 (Lee et al, 2002). NOTCH gain of function mutations are tumourigenic by rendering transformed cells into a less-differentiated immortalized state (Leong & Karsan, 2006;Miele, 2006;Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that FCER2 gene products may exert growth factor activity for B cells (Borland et al, 2007) and that NR4A1 induces apoptosis in response to a broad range of stimuli including PMA and apoptotic BCR signalling (Mapara et al, 1995;Li et al, 2000). Taking into consideration that NOTCH interferes with the apoptotic function of NR4A1 (Lee et al, 2002), the observed upregulation of NR4A1 in response to PMA might mechanistically explain why PMA enhances the apoptotic effect of gliotoxin-mediated NOTCH2 inhibition. This may shed light on the early molecular response of activated CLL cells to gliotoxin and propose CD23 and NR4A1 as valuable biomarkers or surrogate endpoints for monitoring the efficacy of gliotoxin in potential in vivo validation studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The apoptosis-associated nuclear egress of Nur77 has been observed in cancer cells from the lung, ovary, colon, stomach and breast (Dawson et al, 2001;Holmes et al, 2002Holmes et al, , 2003Liu et al, 2002;Wu et al, 2002;Jeong et al, 2003;Kolluri et al, 2003;Wilson et al, 2003;Cao et al, 2004;Jacobs et al, 2004;Lin et al, 2004;Lee et al, 2005). Nur77 mitochondrial localization is also involved in Sindbis virus-induced apoptosis (Lee et al, 2002). Translocation of Nur77 from the nucleus to the cytoplasm is regulated by its unique heterodimerization with RXRa , and once in the cytoplasm, Nur77 targets mitochondria through its interaction with mitochondrial Bcl-2 .…”
Section: Introductionmentioning
confidence: 99%
“…In normal cells, CBF-1 is bound by Notch to regulate the expression of cellular genes involved in cell proliferation (14,187). Lee et al have demonstrated that like Notch, EBNA2 can block orphan nuclear receptor Nur77-mediated apoptosis through interaction between its amino acids 123-147 conserved domain and Nur77 (158). Although Notch signaling functions have been linked to a variety of cellular processes such as adhesion, differentiation, cell proliferation, apoptosis, epithelial to mesenchymal transition, migration, and angiogenesis, Notch can also function as an oncogene or a tumor suppressor in cancer development (14).…”
Section: The Molecular Mechanisms Of Ebv Infection and The Effects Onmentioning
confidence: 99%